2014
DOI: 10.1016/j.jpeds.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers and Angiotensin Converting Enzyme Inhibitors: Comparison of Effects on Aortic Growth in Pediatric Patients with Marfan Syndrome

Abstract: ObjectivesAngiotensin converting enzyme inhibitors (ACEI) have been shown to decrease AGV in Marfan syndrome (MFS). We sought to compare the effect of β-blockers and ACEI on aortic growth velocity (AGV) in MFS.Study designWe reviewed retrospectively all data from all patients with MFS seen at Arkansas Children’s Hospital between January 1, 1976 and January 1, 2013. Generalized least squares were used to evaluate AGV over time as a function of age, medication group, and the interaction between the two. A mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The antihypertensive medication losartan, an angiotensin II (AngII) receptor type 1 (ATR1) blocker, 9 is recommended by current treatment guidelines because of unique antiremodeling properties 7 that are not observed with either angiotensin-converting enzyme inhibitors or b blockers. 9,10 Losartan was shown to decrease the rate of aortic root dilation in rodent models of MFS and in pediatric patients refractory to b-blocker treatment. 7,11 Yet, a large multicenter trial failed to show the expected superiority of losartan treatment over atenolol, 12 which further stirred debate about optimal MFS patient management.…”
mentioning
confidence: 99%
“…The antihypertensive medication losartan, an angiotensin II (AngII) receptor type 1 (ATR1) blocker, 9 is recommended by current treatment guidelines because of unique antiremodeling properties 7 that are not observed with either angiotensin-converting enzyme inhibitors or b blockers. 9,10 Losartan was shown to decrease the rate of aortic root dilation in rodent models of MFS and in pediatric patients refractory to b-blocker treatment. 7,11 Yet, a large multicenter trial failed to show the expected superiority of losartan treatment over atenolol, 12 which further stirred debate about optimal MFS patient management.…”
mentioning
confidence: 99%
“…Currently, the only available and recommended therapeutic approach is treatment of MFS patients with blood pressure lowering medications such as beta blockers (atenolol) or angiotensin-II (ANG II) receptor blockers (ARBs) such as losartan, to reduce the hemodynamic overload in the aortic arch. However, such treatments can only delay the onset of the disease, without preventing the ultimate need for aortic replacement surgery (15,22). The therapeutic approach is more challenging in younger MFS patients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) yr old), as there are no conclusive data on potential side effects of long-term use of such medications in children and young adults.…”
mentioning
confidence: 99%
“… 171 Other clinical studies comparing the effect of ACEIs and β-blockers in MFS nevertheless concluded that ACEIs exert a beneficial effect on central aortic pressure, heart rate and aortic growth rate albeit to a lesser extent. 140 , 172 …”
Section: Current Medical Managementmentioning
confidence: 99%